Key functions for the transferability of a French school-based health promotion intervention - Inès Sartori; Leslie Fonquerne; Camille Riera-Navarro; Daphné Desmoriaux; Cyrille Delpierre; Véronique Régnier Denois (PLoS ONE, 2026)
The “ Alliance for Health ” intervention is a French evidence-based initiative targeting teachers and after-school care staff, aimed at supporting the development of health-promoting environments for primary school pupils. Its initial implementation in 101 schools and 97 municipalities (randomly assigned to receive different levels of training and support) demonstrated promising outcomes. Yet, a critical question remains for broader implementation: under what conditions can the intervention achieve optimal transferability in new contexts? To address this issue, the key functions ( i.e., intervention’s transferable components) were identified and distinguished from their forms ( i.e. , adaptable activities that can be tailored to specific contexts), as conceptualized within the FIC (Functions/Implementation/Context) model. The key functions were co-constructed through an iterative, collaborative process, based on qualitative data (semi-structured interviews conducted with intervention recipients and institutional actors involved in implementation) and on knowledge exchange between project leaders and researchers from various disciplines, following established methods. Seven key functions were identified, covering 4 main dimensions: institutional support (macro-level social influences on health determinants); empowerment of teachers and after-school care staff (inter-professional training and provision of support and resources, micro and meso levels), adaptation to institutional and recipients’ needs and constraints (micro level); and operational alignment and coherent coordination (meso and micro levels). These findings provide actionable recommendations to guide future implementation strategies, supporting the intervention’s replication or scale-up by clarifying which components must remain consistent and which can be adapted to maintain fidelity while enhancing transferability.